Central Asian Republics-Pakistan Relations in a Shifting World: A Neoliberal Perspective (Journal of Politics and International Studies, 2024)
This paper delves into the multifaceted relationship between Pakistan and Central Asian States i.e. Azerbaijan, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, focusing on trade, agreements and institutional cooperation, within the framework of neoliberalism. How neoliberal economic policies have influenced bilateral trade and economic cooperation between these nations? What are the primary challenges and opportunities for Pakistan and Central Asian States in strengthening their geo-economics relations? The study operates under the assumptions that neoliberalism, with its emphasis on market liberalization, privatization, and minimal state intervention, serves as a guiding principle for enhancing economic ties and overcoming traditional barriers to trade and investment. Employing qualitative analysis of policy documents, trade agreements, regional agreements and economic indicators, the research provides a comprehensive understanding of the dynamics at play. Key findings reveal that while CARs and Pakistan have successfully utilized neoliberal policies to bolster economic cooperation, challenges such as state intervention, protectionist measures, insecurity and political instability have hindered the full realization of neoliberal ideals. Despite these obstacles, significant opportunities for deepening economic integration in sectors like energy, tourism, agriculture, textile and digital infrastructure have emerged. The study suggests that decision-makers prioritize the practice and implementation of the already existing vision (i.e. Vision Central Asia, etc.) and agreements (e.g. TAPI, CASA-1000, TTAs, FTAs, etc.) among mentioned countries, encourage public-private partnerships in economic sectors, and strengthen both digital and physical infrastructure to facilitate trade and investment, particularly taking advantage of BRI. New along with existing policies, agreements and measures could significantly enhance the economic relationship between CARs and Pakistan, fostering mutual growth and regional stability.